The Implementation of Finite State Automata Concept in Data Integration Services Submission - Heri Nurcahyo; Windu Gata; Eni Heni Hermaliani; Hafifah Bella Novitasari; Suwanda Aditya Saputra (Universitas Sam Ratulangi, 2022)
The submission of Data Integration Services on regional apparatus in the DKI Jakarta Provincial Government is still processed manually. The data user proposes data integration services by attaching a data analysis requirement document addressed to the Data Producer and a copy to the data guardian. The Problems of manual submitting services are the difficulty of tracking the integration status, filling out the application data analysis form is inappropriate and incomplete, the data integration submission letter is not properly archived, and the results of the coordination betwen users and data producers are not properly documented.This study aims to design an application for submitting data integration services by applying the concept of Finite State Automata which is expected to provide convenience and benefits for data users in data integration submission, facilitate data producers in verifying data integration submission and facilitate the Department of Communication, Informatics, and Statistics of DKI Jakarta as data guardian in providing data integration services for Regional Apparatus in the DKI Jakarta Provincial Government.